Improving Economic Resilience Through Social Entrepreneurship - Kemal Al Kindi Mulya; Ramadhian Erva Sandya (STMIK Indonesia Banda Aceh, 2026)
This paper explores the role of social entrepreneurship in strengthening economic resilience, particularly within the Indonesian context. The study aims to (1) promote synergistic collaboration among government entities, the private sector through Corporate Social Responsibility (CSR) initiatives, and civil society to overcome structural funding challenges, and (2) enhance the involvement of practitioners and academics in fostering community-driven enterprises. Employing a descriptive qualitative method through literature review, this study finds that while Indonesia possesses substantial human capital and natural resources, the potential of social entrepreneurship remains underutilized. Strengthening this sector could significantly contribute to achieving equitable economic development and long-term national resilience.